Dynamics of biochemical indexes at experimental invazuvanni of crawls by an exciter - Манжос, О. Ф.; Передера, О. О.; Лавріненко, І. В.; Передера, Р. В.; Жерносік, І. А. (Scientific Progress & Innovations, 2012)
The development of hepatic form eymeriozu rabbits characterized by biochemical changes in serum parameters. Indicators of enzymes of serum AST, ALT, LDH HHTP, LF in the early stages of the disease were not specific, but only pointed to the reactions of liver cells and biliary tract. At 6 th day of the experiment, despite the absence of clinical signs recorded increased activity of ALT, AST, HHTP, indicating violation of the structure of the liver. Preferential increase in activity of ALT over AST in patients with rabbits at the 16 th day of research is the result of acute inflammation in the liver parenchyma. Higher values HHTP, ALT, AST in serum corresponds to the presence of cytolysis syndrome that develops after disruption of cell integrity, which includes data from enzymes: hepatocytes and biliary tract epithelial cells.